From Vietnam, with love : brides for sale. - Sim, Melvin Khia Liang. (2009)
This report documents the background of the Vietnam Bride matchmaking industry both in Singapore and Vietnam. It also details the process of working on this photojournalism project from even before the click of the shutter right down to the final printing of the book and photo exhibition. It covers, as well, the challenges and lessons learnt along the way.